A formação continuada de professores para educação preventiva e promoção de saúde - Moura, Rosangela Aparecida Cemino (2009)
The objective of this study is to analyze the social representations of the concepts, purposes and triggered actions on the teacher s graduation processes to preventive education and health promotion, from a graduation project, going by on State Public Net. The perspective abstract was a link between the social representation abstracts and the social change, under Professional ID vision. The used approach was qualitative, and the procedures were: a) documents study of graduation Project; and b) semi-structured interview with the proposal coordinators. The social representations were researched, from communication processes feeling between them and the teachers on building on a new health and prevention Idea. About the organization and datas analysis, it was used 3 conceited categories: Me (graduator), the Other (teacher) and the Object (the graduation), inspired by Marková (2006) and, from these, the results were: On the net, the teacher s graduators in health prevention belong to several hierarchical levels and this difference is not considered by graduation Project. The graduation objective is to establish the self-care as the graduation for the student in the social-constructivist perspective, and wish that the teacher manages this process, constituting and reconstituting their professional of identifying traces including the preventive education as an item of their educative task, assuming the co-authorship of this process. However, on teachers education if it opts to the formation in cascade, from the multiplication of expert s concepts, adopting the transmissible perspective, without revision of the graduators of identifying traces, that is kept on the ¨of what¨ standardization and how it must me taught. The graduator s work social representations are based on functionalist vision, where the authority is verticalized, guided by the hierarchical logic, aiming at to consist as orientation for the behavior of the teacher. The relation between groups emphasizes the dependence, and the action model affirms itself for the carepaternalistic position